Psychiatric Diagnosis as Newly Discovered Evidence in Ireland - Noonan, Luke (The Wrongful Conviction Law Review, 2025)
This article considers how courts in Ireland have responded to newly discovered evidence that a defendant was suffering from a mental disorder at the time of the offence. Where such evidence was not known to the jury, there is a risk that a wrongful conviction may have occurred. When psychiatrists examine a defendant for the purposes of criminal proceedings, they may only have had limited time to study and diagnose the defendant. Sometimes, the defendant’s subsequent symptoms and presentation can lead to a psychiatrist revising their original diagnosis. In Ireland, a defendant can make an application arguing that this newly discovered fact shows that there has been a miscarriage of justice in relation to the original conviction. It appears that Irish courts will only accept such applications in exceptional circumstances. This article discusses the recent Court of Appeal decisions in People (DPP) v Abdi (no 2) and People (DPP) v McGinley. It analyses the reasoning of the judgments and seeks to identify what general principles can be derived from the decisions that can be used to inform future applications.